Criteria for return to running after anterior cruciate ligament reconstruction: a scoping review. Issue 22 (2nd May 2018) - Rambaud, Alexandre J M; Ardern, Clare L; Thoreux, Patricia; Regnaux, Jean-Philippe; Edouard, Pascal
Abstract : Objective: To describe the criteria used to guide clinical decision-making regarding when a patient is ready to return to running (RTR) after ACL reconstruction. Design: Scoping review. Data sources: The MEDLINE (PubMed), EMBASE, Web of Science, PEDro, SPORTDiscus and Cochrane Library electronic databases. We also screened the reference lists of included studies and conducted forward citation tracking. Eligibility criteria for selecting studies: Reported at least one criterion for permitting adult patients with primary ACL reconstruction to commence running postoperatively. Results: 201 studies fulfilled the inclusion criteria and reported 205 time-based criteria for RTR. The median time from when RTR was permitted was 12 postoperative weeks (IQR=3.3, range 5–39 weeks). Fewer than one in five studies used additional clinical, strength or performance-based criteria for decision-making regarding RTR. Aside from time, the most frequently reported criteria for RTR were: full knee range of motion or >95% of the non-injured knee plus no pain or pain <2 on visual analogue scale; isometric extensor limb symmetry index (LSI)>70% plus extensor and flexor LSI>70%; and hop test LSI>70%. Conclusions: Fewer than one in five studies reported clinical, strength or performance-based criteria for RTR even though best evidence recommends performance-based criteria combined with time-based criteria to commence running activities following ACL reconstruction.